Faktor-faktor yang mempengaruhi kesulitan membaca Al-Qur’an peserta didik TPQ Hidayatus Salam Perumnas Jabung - Hasna, Nida Asyfiatul (Maliki Interdisciplinary Journal, 2024)
At the initial level, a child learns to read the Al-Qur’an after going through several basic levels of introduction regarding the letters of the Al-Qur’an, they will encounter several difficulties in the initial process of assembling the readings in the Al-Qur’an. This obstacle was found by several students at TPQ Hidayatus Salam Perumnas Jabung. This research aims to find the forms of difficulties experienced by students when reading the Koran and the factors that influence them. This research is a type of qualitative research. Data collection techniques used note-taking and interview techniques. The research results found 4 forms of difficulty reading the Al-Qur’an by TPQ Hidayatus Salam students and 4 factors that influenced them with the same 2 factors.